Preparing New Ceramic Membranes from Syrian Zeolite Coated with Silver Nanoparticles to Treatment Wells Water (Baghdad Science Journal, 2023)
As a result of the exacerbation of the problem of water pollution, research was directed towards studying the treatment using ceramic membranes, which proved to be highly effective in treating all water sources. The research aims to study the possibility of preparing a new type of ceramic membranes from Syrian zeolite that was not previously used in this field. In this research, ceramic membranes were prepared from Syrian raw zeolite in several stages. Zeolite sample was characterized, grinded, mixed with boric acid, pressed to form desks, treated thermally according to experiment program, finally coated with silver nanoparticles. Specifications of prepared membranes were determined according to reference methods, effectiveness of prepared membranes were tested in well water handling, that water sample was filtrated through prepared membranes, and then it   type MAC, so removal degree was 100%, While removal degree was 97% for bacterial strains on Agar with type PCA, 93% on Agar with type PDA which were conformed to Syrian standard /45 /2007.Specifications of prepared membranes were determined according to reference methods, effectiveness of prepared membranes were tested in well water handling, that water sample was filtrated through prepared membranes, then it was Characterized after treatment.Results showed that prepared zeolite membranes were high effectiveness through decrease chemical and microbial pollutants which were conformed to Syrian standard /45 /2007